A Novel Approach for Unveiling Layered Geometric Patterns in Noisy Unsupervised Data: A Study on Drug-Like Molecules - Cavalcanti, Luiz C. D.; Rios, Ricardo A.; Lopes, Tiago J. S.; Rios, Tatiane N. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
Identifying meaningful examples in datasets where most or all data belong to a single category is a common challenge in Machine Learning (ML). In many real-world scenarios, such as in science, medicine, and industry, data for the target class is often abundant, while data from other classes is scarce or missing. This makes it difficult for ML models to differentiate between what belongs to the target class and what does not. This paper presents a novel approach to address this issue by combining clustering and geometric analysis techniques. We develop a one-class classification method capable of detecting when a sample belongs to the target class, even in the absence of labeled data from other classes. The proposed method is applied to a curated dataset containing the chemical properties of 1,615 drug molecules approved by U.S. Food and Drug Administration (FDA), offering a valuable resource for future research. Our findings indicate that integrating geometric and density-based insights improves generalization and risk estimation in one-class learning tasks, providing a robust solution for analyzing noisy, unlabeled data.